PERAN PUBLIC RELATION DINAS KEBUDAYAAN PARIWISATA DAN KEPEMUDAAN OLAHRAGA DALAM MENINGKATKAN PELAYANAN PARIWISATA PANTAI SORAKE KABUPATEN NIAS SELATAN - Rosmei Giawa; Elok Perwirawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
This study aims at determining the role of public relations Department of Culture, Tourism and Youth in Sport in improving tourism services for the coast of Sorake in South Nias Regency. The method to this research is to use a qualitative approach. The results obtained are the role of the Public Relations Department of Culture, Tourism and Sports Youth in improving Sorake Beach services, South Nias Regency is still not well implemented duei in to the difficulty of building communication with local communities in terms of cooperation in to maintaining the supporting large development processes and facilities and implementation of the program activities. Supporting factors fort to in tourism to Sorake Beach are supported by several components related to tourist activities such as the condition of the tourist objects, social facilities in tourist objects, ease of transportation, security and orderliness of tourist objects, as well as government policies related to the tourism sector while the inhibiting factor is the lack of the guidance, socialization, training for the community around the Sorake beach so that people experience various misunderstandings against tourists visiting the beach and some of the community are not willing to give their land to be used as a tourist attraction.